Screening for human trafficking among refugees in Germany: determining prevalence and test accuracy of a modified version of the adult human trafficking screening tool - Tambini Stollwerck, Estella; Dönnhoff, Ivo; Friederich, Hans-Christoph; Nikendei, Christoph (Research Square, 2023)
Background Human trafficking consists of the exploitation of a person by means of force, intimidation or deceit. Though it occurs all over the world, its true extent is still unknown. Refugees are especially vulnerable to human trafficking due to language barriers and difficult living...